Volatility dependence of Henry's law constants of condensable organics: Application to estimate depositional loss of secondary organic aerosols. Issue 13 (16th July 2014) - Hodzic, A.; Aumont, B.; Knote, C.; Lee‐Taylor, J.; Madronich, S.; Tyndall, G.
Abstract The water solubility of oxidation intermediates of volatile organic compounds that can condense to form secondary organic aerosol (SOA) is largely unconstrained in current chemistry‐climate models. We apply the Generator of Explicit Chemistry and Kinetics of Organics in the Atmosphere to calculate Henry's law constants for these intermediate species. Results show a strong negative correlation between Henry's law constants and saturation vapor pressures. Details depend on precursor species, extent of photochemical processing, and NOx levels. Henry's law constants as a function of volatility are made available over a wide range of vapor pressures for use in 3‐D models. In an application using the Weather Research and Forecasting model coupled with Chemistry (WRF‐Chem) over the U.S. in summer, we find that dry (and wet) deposition of condensable organic vapors leads to major reductions in SOA, decreasing surface concentrations by 50% (10%) for biogenic and 40% (6%) for short chain anthropogenic precursors under the considered volatility conditions.